Mechanical Behavior and Microstructural Study of Biocemented Sand under Various Treatment Methods - Xuecheng Gao; Shaokang Han; Yang Yang; Wengang Zhang; Tan Zou; Liang Cheng (Geofluids)
Biocementation mainly relies on the formation of calcium carbonate to bind soil particles. This paper investigates the effectiveness of biocementation in terms of treatment methods. The previously established two-phase methods are compared with newly developed one-phase-low-pH methods on their mechanical behavior and microstructure. The one-phase-low-pH methods present a higher urease fixation rate than two-phase methods, highlighting the cost-effectiveness of this method. A modified one-phase-low-pH using CH3COOH is also compared with HCl-based one-phase-low-pH method. The results show that the morphology and size of precipitated crystals have a great influence on strength development. An optimized treatment method based on the one-phase-low-pH method is also established, which is accomplished via the injection of 5 U/ml of bacterial culture together with 2 M of cementation solution during each treatment. After four times of treatments, a total of 7% cumulative calcium carbonate content can be obtained with an unconfined compressive strength of 2.15 MPa.